Calculation of The Nuclear Matter Density Distributions and Form Factors For The Ground State of P 12 PBe and P 14 PBe Nuclei - Radhi, R.; Hamoudi, A.; Majeed, W. (Iraqi Journal of Science, 2024)
The ground state charge, neutron and matter densities for two-neutron halo nuclei P12PBeand P14PBe are calculated within a two- frequency shell model approach. In the description ofthe halo nuclei it is important to take into account a model space for P10PBe and P12PBe differentfrom the two halo neutrons which have to be treated separately in order to explain theirproperties. The structures of the halo P12PBe and P14PBe nuclei show that the dominantconfigurations when the two halo neutrons distributed over the 1d shell orbits. ElasticCoulomb scattering form factors of these two exotic nuclei are also studied through thecombination of the density distributions of the P10PBe, P12PBe core and the two halo neutrons.The effects of the neutron halos on the electron scattering form factors are explored. Theform factors for the two exotic P12PBe and P14PBe nuclei are compared with those of the stableP9PBe nuclei. It is found that the difference in the calculated charge form factors between haloand stable nuclei is attributed mainly to the difference in the center of mass correction whichdepends on the mass number and the size parameter (b).PACS number(s): 25.30.Bf;21.60.Cs;21.10.Gv;27.20+n.